Hubert who? : war hero. Polar explorer. Spy. The incredible life of unsung adventurer Hubert Wilkins /: war hero. Polar explorer. Spy. The incredible life of unsung adventurer Hubert Wilkins. (2011) - Andrews, Malcolm, 1944-
No abstract available